Innovation in Electronic Payment Adoption : The Case of Small Retailers - World Bank Group (World Economic Forum, Geneva and World Bank, Washington, 2016)
This report aims to deepen the understanding of barriers to and incentives for the acceptance and use of electronic payments, from the perspective of micro, small and medium retailers (merchants). Developing and accelerating acceptance of electronic payments by these merchants is essential to expanding financial access. A basic transaction account for payments and deposits is considered an entry point to the formal financial system, and can act as a gateway for individuals to adopt other relevant financial services they need to smooth their consumption and manage income shocks. However, equipping individuals with only basic transaction accounts is not sufficient. The use case for payment services becomes increasingly effective as individuals gradually move to a cashless economy, where electronic payments are widely accepted for regular and frequent purchases. The report highlights important dimensions to consider in the efforts to expand electronic payments for merchants.